Appendicoliths: the neglected stones (Journal of Patan Academy of Health Sciences, 2017)
Introductions: Cases of colic of the vermiform appendix have been rarely described or diagnosed. Appendicoliths cause acute appendicitis and appendicular perforation. It is still not clear whether appendicoliths cause appendicular colic in the absence of acute appendicitis.Methods: A cross sectional study that included appendectomy done for recurrent appendicitis or chronic right iliac fossa pain. Histology reports were reviewed. The presence of an appendicolith in the report was noted.Results: Thirty-two cases of recurrent appendicitis and chronic right iliac fossa pain were included. Twenty-four patients (75%) had fecoliths in the histology specimens. Eight patients (25%) who presented with appendicular colic without signs of appendicitis were further evaluated.Conclusions: Majority of patients with chronic or colicky right iliac fossa pain had appendicoliths.